2017
DOI: 10.1007/s10433-017-0424-5
|View full text |Cite
|
Sign up to set email alerts
|

Career histories as determinants of gendered retirement timing in the Danish and Swedish pension systems

Abstract: After reforms in pension systems had taken place in most European countries within the last two decades, the concern was raised that women may be disadvantaged by these reforms. It is suggested that they are faced with a higher financial need to work longer. Retrospective data from SHARELIFE are used to run an event history analysis on the timing of the final employment exit, separately for gender, country and exit cohort. This study aims to disentangle the influence of gendered labour markets and pension regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 41 publications
3
28
1
Order By: Relevance
“…There was no evidence that having had children affected career length and retirement timing any differently for women and men in Finland. This is in contrast with findings from a recent study on two other Nordic countries, Sweden and Denmark, where longer career breaks for women were associated with later retirement (König, 2017).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…There was no evidence that having had children affected career length and retirement timing any differently for women and men in Finland. This is in contrast with findings from a recent study on two other Nordic countries, Sweden and Denmark, where longer career breaks for women were associated with later retirement (König, 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…At the same time, shorter careers may mean lower levels of pension accrual. According to the 'compensation hypothesis', this may lead to women, especially in dual earner societies, deferring retirement until it is financially feasible (Finch, 2014;König, 2017). This effect might be stronger for divorced women who (re)enter the labour market after separation (Fasang, Aisenbrey and Schömann, 2013;Finch, 2014).…”
Section: Gendered Life Coursesmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, although our focus was to compare welfare regimes, our additional comparisons to see country-specific differences within the same welfare regimes found different effects of part-time work between Denmark and Sweden; Danish mothers who have worked mostly part-time are more likely to intend to retire early. This finding is consistent with König (2017), who found that longer years in part-time work lead to the early retirement of Danish women while delaying the retirement of Swedish women. The country-specific differences within the social democratic regime may be due to differences in pursued family policies (Gupta et al, 2008) as equalisation of parents' use of parental leave is more promoted in Sweden than Denmark (Pylkkänen and Smith, 2004).…”
Section: Discussionsupporting
confidence: 92%